Феномен жіночої релігійності з погляду соціології релігії - Колосок, Тетяна Святославівна; Колосок, Татьяна Святославовна; Kolosok, Tetiana S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Зростаюча активність жінок у сфері релігії й пошуку духовної самореалізації актуалізувала тему вивчення жіночої релігійності, зростання рівня якої обґрунтовується в цій праці. Висновки з приводу вищої релігійності жінок здійснюються на основі кількісних методів соціологічного аналізу. Також з’ясовано, що нині в межах соціології релігії напрацьовано теоретичні підходи, які пояснюють відмінності в релігійності чоловіків і жінок (економічні теорії, марксистська теорія й психосоціальні теорії), але спроби емпірично їх перевірити не принесли однозначних висновків або були неуспішними. Modern woman has freedom of choice of spiritual self-realization ways, both within the framework of traditional religions and neo-religious movements. Growing activity of women in the religion sphere and search of spiritual self-realization actualizes the selected research subject. The aim of the article is to analyze phenomenon of woman religiousness, its reasons from view point of religion sociology. It is established in the article that the level of religious activity of women grew. It worth taking into account that religiousness is not limited to church activity, that is why research of religion should take into account faith and supernaturalism that is out of the organized church organization. Conclusions concerning the higher religiousness of women are drawn on the basis of quantitative methods of sociological analysis. The Ukrainian researchers N. Dudar, В. Melnyk, М. Parashchevin, S. Salnikova, studying the religiousness of Ukrainian society assert that women are more religious than men (75 % against 57 % in 2013). Researchers consider that such state can be explained by psycho-physiological and mental features of different sexes representatives. It is marked in the article, that the numerous sociological researches conducted in various state formations confirm the thesis about women’s high religiousness. It is found out by the author, that presently within the framework of religion sociology theoretical approaches that explain differences in the religiousness of men and women are turned out: economic theories, Marxist theory and psycho-social theories. Attempts to check these theories in empiric way have not brought unambiguous conclusions or have not been successful.
Phenomenon of Women Religiousness from the View Point of Religion Sociology
Keywords: релігійність; соціологія релігії; феномен жіночої релігійності; religiosity; religion sociology; phenomenon of woman religiousness